Non‐linear dynamic soil‐structure interaction analysis of buildings - Gouasmia, Abdelhacine; Djeghaba, Kamel (Technological and Economic Development of Economy, 2007)
The objective of this research is to evaluate the effects of soil‐structure interaction (SSI) on the modal characteristics and on the dynamic response of structures. The stress had an impact on the overall behaviour of five storeys reinforced concrete (R/C) buildings typically encountered in Algeria. Sensitivity studies are undertaken in order to study the effects of frequency content of the input motion, frequency of the soil structure system, rigidity and depth of the soil layer on the dynamic response of such structures. This investigation indicated that the rigidity of the soil layer is the predominant factor in soil‐structures interaction and its increases would definitely reduce the deformation of the R/C structures. On the other hand, increasing the period of the underlying soil will cause an increase in the lateral displacements at storey levels and create irregularity in the distribution of storey shears. Possible resonance between the frequency content of the input motion and soil could also play an important role in increasing the structural response. Nalinijinė dinaminė grunto, slūgstančio po pastatais, struktūros pokyčių analizė Santrauka. Šio darbo tikslas – įvertinti grunto struktūros pokyčiu įtaka esamiems statiniams. Dėmesys sutelktas į procesus, kurie vyksta penkiaaukščių gelžbetoninių pastatų, dažnai statomų Alžyre, konstrukcijose. Atlikti jautrumo tyrimai, siekiant nustatyti, kaip grunto virpesių dažnis, standumas ir sluoksnio gylis veikia minėtų statinių konstrukcijas. Tyrimas atskleidė, kad grunto sluoksnio standumas yra svarbiausias veiksnys, sukeliantis grunto struktūros pokyčius ir galintis padidinti deformacijas gelžbetoninių pastatų konstrukcijose. Kita vertus, dideli po pamatais slūgsančio grunto poslinkiai sukels šoninius pastato poslinkius, dėl to persiskirstys šlyties sukelti įtempiai. Galimas drebėjimų judesiu ir grunto savųjų svyravimų dažnių rezonansas taip pat gali sukelti didesnį poveikį konstrukcijoms. Reikšminiai žodžiai: pamatai, gelžbetoninis remas, grunto struktūros pokyčiai, standumas, tiesioginis metodas, baigtiniu elementu metodas. First Published Online: 21 Oct 2010